RTS de l'Estrie – CHU de Sherbrooke - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Redefining the Black Experience in Montreal: One Institution at a Time - The Project Woke Interns (Black Community Resource Centre (BCRC), 2020)
Project Woke interns identified and investigated three critical themes affecting the Black community in Montreal. An analysis of societal issues and Canada’s Anti-Racism Strategy Project revealed harmful anti-human rights gaps affecting the Black Community. The findings from several consultations further validated these gaps. A comprehensive list of recommendations is included along with next steps as a continuation to advance Black human rights in Montreal, and elsewhere, along with the support of government and non-government actors.

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Children 0 to 5 and their Parents : RTS de l'Estrie – CHU de Sherbrooke - Community Health and Social Services Network (CHSSN) (2016)

Profil sociodémographique des enfants de 0 à 5 ans et de leurs parents RTS de l'Estrie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Le développement de la petite enfance (DPE), est une pierre angulaire du développement humain et l’enfance, est considérée comme étant la phase de développement la plus importante de la durée de la vie d’un individu. Les résultats en matière de développement à ce premier stade de la vie affectent le niveau de santé et de bien-être dont jouit une population dans son devenir. Le développement de la petite enfance est un déterminant social de la vie des communautés et il s’agit d’un processus qui est particulièrement sensible à des déterminants sociaux tels que la situation socioéconomique des familles avec des enfants de 0 à 5 ans et leur environnement social, l’accès aux services sociaux et de santé, la compétence en communication et l’alphabétisation ainsi que l’accès aux réseaux locaux de soutien social.

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l’Estrie – CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Estrie – CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

English-speaking Seniors : RTS de l'Estrie - CHUS - Townshippers' Association (2016)

Socio-demographic Profile of Children Aged 0 to 5 and Their Parents RTS de l'Estrie - Pocock, Joanne (Community Health and Social Services Network (CHSSN))
Early child development (ECD) is a cornerstone of human development and childhood and is considered to be the most important developmental phase of an individual’s lifespan. The developmental outcomes of this early phase of life impact the level of health and well-being enjoyed by a population in its future. Early child development is a social determinant of the health of communities and it is a process that is particularly sensitive to social determinants like the socio-economic status of families with children aged 0-5 and their social environment, access to health and social services, communication competency and literacy and access to local social support networks.
Keywords: Official Language Minority Community (OLMC)